2019
DOI: 10.1371/journal.pone.0218730
|View full text |Cite
|
Sign up to set email alerts
|

Junín virus induces autophagy in human A549 cells

Abstract: Autophagy, a highly regulated degradative process that promotes cellular homeostasis, is increasingly recognised as a fundamental component of the cellular response against viral infection. In this study, we investigated the role of autophagy during Junín virus (JUNV) multiplication using human A549 cells. We found that JUNV infection induces an increment of the LC3-II/LC3-I ratio, an accumulation of punctate pattern in RFP-LC3-transfected cells and the colocalisation of viral nucleoprotein and LC3 protein, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 76 publications
2
19
0
Order By: Relevance
“…The role of autophagy during arenavirus infection is largely unknown, but recent research has provided evidence of a proviral role for autophagy. Two groups observed that both virulent and attenuated strains of JUNV induce autophagy early in infection [86,87]. Induction of autophagy prior to infection results in increased NP expression [87].…”
Section: Arenavirus Subversion Of Other Host Antiviral Defensesmentioning
confidence: 99%
See 4 more Smart Citations
“…The role of autophagy during arenavirus infection is largely unknown, but recent research has provided evidence of a proviral role for autophagy. Two groups observed that both virulent and attenuated strains of JUNV induce autophagy early in infection [86,87]. Induction of autophagy prior to infection results in increased NP expression [87].…”
Section: Arenavirus Subversion Of Other Host Antiviral Defensesmentioning
confidence: 99%
“…Two groups observed that both virulent and attenuated strains of JUNV induce autophagy early in infection [86,87]. Induction of autophagy prior to infection results in increased NP expression [87]. The OW MOPV also transiently induces autophagy during the first two days of infection, though LASV does not [88].…”
Section: Arenavirus Subversion Of Other Host Antiviral Defensesmentioning
confidence: 99%
See 3 more Smart Citations